Contents Development of Library Signage Manual in Korea - Ahn, In-Ja (International Journal of Knowledge Content Development & Technology, 2011)
There is an increase in the need of an unified manual for library signage system, due to recent increase in library construction or remodeling. This paper, therefore, can be a basic research to develop library signage system manual. Based on an anual released from KLA and the sum of opinions of expert groups, this research proposes a concrete list of contents for library signage system manual as follows. First, there is a need of theoretical basis of library signage system. Second, for the actual practices of signage system, planning, check list, and standard terms shall be necessary. URL: http://ijkcdt.net/xml/00642/00642.pdf